PEPAMARKER: a multicenter cohort study protocol on predictive biomarkers of affective vs. non-affective trajectories in first-episode psychosis - Terrisse, Raphaël; Lemey, Christophe; Kim-Dufor, Deok-Hee; Miglianico, Louise; Stéphan, Florian (Frontiers in Psychiatry, 2026)
BackgroundPsychosis is a severe and disabling mental disorder with peak incidence in late adolescence and early adulthood. Following a first-episode psychosis (FEP), clinical trajectories diverge into affective psychoses or non-affective psychoses. At illness onset, differentiation between these trajectories is frequently impossible, which results in delayed treatment adaptation and increased relapse risk. Predictive biomarkers, particularly linguistic and inflammatory markers, may help refine early diagnosis and personalize care.ObjectiveThe primary objective of the PEPAMARKER study is to develop a predictive model based on prosodic markers to identify affective vs. non-affective trajectories at 2-year follow-up of patients with first-episode psychosis.MethodsPEPAMARKER is a prospective, multicenter, minimal-risk study conducted in five psychiatric centers in France. A total of 217 participants aged 15–30 years with FEP will be enrolled and followed for 24 months. At baseline, data will be collected through clinical interviews (audio-recorded and transcribed), standardized rating scales, and inflammatory markers. Prosodic markers will constitute the primary predictors. Secondary predictors include syntactic/semantic features, inflammatory biomarkers, and clinical rating scales. The primary endpoint is affective vs. non-affective evolution of psychosis at 2 years. Statistical analyses and logistic regression models will be conducted along with the assessment of internal validity.Expected impactThe study aims to provide accessible predictive tools using clinical interview recordings and basic blood tests to improve early differentiation of psychosis trajectories, which is crucial to a timely treatment adaptation and a reduction in relapse risk.Clinical Trial Registrationhttps://clinicaltrials.gov/, identifier NCT05384392.